(untitled) - Kawabata, Hiroto (Tokyo, Japan, 2020)
This book grew out of an effort to gain a better understanding of the peoples who populated Asia in ancient times and to present these findings from a modern Homo sapiens perspective.
Keywords: Con người,Human beings; Nguồn gốc,Origin